Islamisasi dan Kristenisasi di Manggarai: Mengendus Jejak Monisme Moral Pada Muslim & Katolik di Manggarai - Hironimus Bandur (STIPAS St. Sirilus Ruteng, 2020)
Reading the socio-historical phenomenon of moral monism in Manggarai, must be started from the expansion of Islamization and Christianization. Islamization and Christianization had an effect on the growth of Islamism and Catholicism. The main character of Islamization and Catholicism is the claim of the exclusive truth. Each of them claimed that their religion only is the most true and logic, therefore it must be adhered, then the other one is wrong and ilogic, therefore it must be left. This preaching reinforced the concept of moral monism to each individual. In this paper, the author found that the history of Islamization and Christianization in Manggarai had formed the monism moral in religious life, however, moral monism in Islamism is different from moral monism in Catholicism. The phenomenon of moral monism in religious teaching can disrupt Muslim and Catholic relations, including the Manggaraian. Prevention efforts must be made by various social elements such as the local government, the religious teachers, and Moslim-Catholic community in Manggarai. The response of the great Catholic and Moslem figures: Pope Francis and Grand Shaykh Ahmad Thayyip in the UAE, that is included, Abu Dhabi Document would be implemented in religious life.